CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Solve for $$x$$: $$\displaystyle \frac{3x}{4}-\frac{(x-1)}{3}=\frac{(x-2)}{2}$$.


A
9
loader
B
14
loader
C
16
loader
D
11
loader

Solution

The correct option is C $$16$$
Given, $$\displaystyle \frac{3x}{4}-\frac{(x-1)}{3}=\frac{(x-2)}{2}$$
L.C.M. of denominator $$=12$$
$$\therefore $$ Multiplying each term by $$12$$, we get 
$$\displaystyle 12\times \frac{3x}{4}-12\times \frac{(x-1)}{3}=12\times \frac{(x-2)}{2}$$
$$\Rightarrow 9x-4(x-1)=6(x-2)$$
$$\Rightarrow 9x-4x+4=6x-12$$
$$\Rightarrow 5x+4=6x-12$$
$$\Rightarrow x=16$$
Hence, required value of $$x$$ is $$16$$.

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image